The Effect of Differentiation of Human Dental Pulp Stem Cells to Glial Cells on the Sensory Nerves of the Dental Pulp - Yan Liu; Yuxi Zou; Xinxin Liu; Yushan Wang; Jing Sun; Changyong Yuan; Penglai Wang (International Journal of Dentistry)
Regeneration of sensory nerves is challenging in dental pulp regeneration. Schwann cells (SCs) are essential glial cells conducive to regenerating sensory nerve, but their source is scarce. The aim of the protocol was to investigate the regenerative potential of Schwann-like cells derived from dental pulp stem cells (SC-DPSCs) for sensory nerve regrowth. SC-DPSCs were generated from dental pulp stem cells using a three-step protocol. The expression of key markers, including myelin basic protein, S-100, and p75 neurotrophin receptor, was analyzed. Primary trigeminal neurons were cultured, and the expression of neurofilament 200, β-tubulin III, and microtubule-associated protein 2 was assessed. Simultaneous culture experiments were conducted to evaluate trigeminal neuron growth in the presence of SC-DPSCs. In addition, mRNA sequencing was performed to identify key genes involved in the differentiation process, highlighting prostaglandin-endoperoxide synthase 2 (PTGS2) as a potential candidate. The results demonstrated that SC-DPSCs expressed characteristic SCs markers and facilitated axonal growth in rat trigeminal nerves. Differentiated SC-DPSCs secreted elevated levels of nerve growth factors, including brain-derived neurotrophic factor and neurotrophin-3, promoting the growth of trigeminal nerve axons. These findings suggest the regenerative potential of SC-DPSCs in dentin–dental pulp complex; PTGS2 is considered a crucial gene in this differentiation process.